Development of Selection Criteria on Bean Weight Character of Cocoa (Theobroma cacaoL.) through Path Analysis Approach - Indah Anita Sari; Agung Wahyu Susilo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
Path coefficient analysis is frequently used for development of selection criteria on various type of plants. Path analysis on this research was conducted to find the selection criteria of yield component which directly affect bean weight. In addition to the value of path analysis coefficient, genetic variation coefficient, heritability and the value of genetic progress were also studied. The study was conducted at the Indonesian Coffee and Cocoa Research Institute. The research used randomized complete block design consisting of 14 accession numbers and each consisting of three replications. Pod girth, pod length, pod weight, wet beans weight per pod, number of normal beans per pod, number of abnormal beans per pod, dry weight per normal bean, and shell content were observed. The results showed that the pod weight character had an important role in determining the dry weight of normal bean. The character had a positive genotype correlation coefficient values which was high and significantly different (r=0.46) for dry weight per normal bean, considerable direct influence (P=0.479), moderate of the genotype variation coefficient (9.6%), and high genetic progress (95.23). Character of wet bean weight per pod could also be used indirectly for the selection criteria for dry weight per normal bean based on genetic variation coefficient value (11.88%), genetic progress value (82.48), and direct effect on dry weight per normal bean had positive value (P=0.006). Key words: Selection criteria, dry weight per bean, path analysis,Theobroma cacaoL.